2012
DOI: 10.1029/2012gl050890
|View full text |Cite
|
Sign up to set email alerts
|

The Arctic Ocean warms from below

Abstract: [1] The old ($450-year isolation age) and near-homogenous deep waters of the Canada Basin (CBDW), that are found below $2700 m, warmed at a rate of $0.0004 C yr À1between 1993 and 2010. This rate is slightly less than expected from the reported geothermal heat flux (F g $ 50 mW m À2 ). A deep temperature minimum T min layer overlies CBDW within the basin and is also warming at approximately the same rate, suggesting that some geothermal heat escapes vertically through a multi-stepped, $300-m-thick deep transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 33 publications
0
31
2
Order By: Relevance
“…Hydrological features such as the θ-S convexity and O 2 minimum observed within the DTL at the MB stations also support exchanges of CB deep waters toward the MB (Figures 4, 5h, and 9d). Although the direction of exchanges we suggest here conflicts with former hydrological study conclusions that invoked a dominant flux of DTL water above the Mendeleev/Alpha Ridge from the MB toward the CB (e.g., Carmack et al, 2012;Rudels, 2009), Swift et al (1997) (Figures 9b and 12c), we agree with Middag et al (2009) and Roeske et al (2012) that MB bottom water is also made of some colder and fresher Amundsen Basin Deep Water (ABDW) that likely came over the Lomonosov Ridge (between 2,000 and 2,500 m) and sank due to its higher density than the local bottom waters (Timmermans et al, 2005).…”
Section: Lateral Exchanges In Other Areas Of the Amerasian Basin 54contrasting
confidence: 99%
“…Hydrological features such as the θ-S convexity and O 2 minimum observed within the DTL at the MB stations also support exchanges of CB deep waters toward the MB (Figures 4, 5h, and 9d). Although the direction of exchanges we suggest here conflicts with former hydrological study conclusions that invoked a dominant flux of DTL water above the Mendeleev/Alpha Ridge from the MB toward the CB (e.g., Carmack et al, 2012;Rudels, 2009), Swift et al (1997) (Figures 9b and 12c), we agree with Middag et al (2009) and Roeske et al (2012) that MB bottom water is also made of some colder and fresher Amundsen Basin Deep Water (ABDW) that likely came over the Lomonosov Ridge (between 2,000 and 2,500 m) and sank due to its higher density than the local bottom waters (Timmermans et al, 2005).…”
Section: Lateral Exchanges In Other Areas Of the Amerasian Basin 54contrasting
confidence: 99%
“…Both an approximate heat budget (Timmermans et al 2003;Carmack et al 2012) and an overturn analysis of the interfaces (Timmermans et al 2003) indicate that F H is less than that predicted using the parameterization of Kelley (1990), however, it is not known by exactly how much. Both an approximate heat budget (Timmermans et al 2003;Carmack et al 2012) and an overturn analysis of the interfaces (Timmermans et al 2003) indicate that F H is less than that predicted using the parameterization of Kelley (1990), however, it is not known by exactly how much.…”
Section: Oceanic Implicationsmentioning
confidence: 95%
“…A number of previous studies in polar regions have speculated on staircases in which the heat fluxes appear to be significantly less than the laboratory-derived laws (Howard et al 2004;Timmermans et al 2003;Polyakov et al 2012;Carmack et al 2012). A number of mechanisms may be important for the observed flux reduction, such as a mean shear present across the interfaces (Polyakov et al 2012) or lateral effects (Kelley et al 2003).…”
Section: Oceanic Implicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 1969, Neal et al already found strong layering structures suggestive double-diffusive convection in abyssal AO. It was supposed to be the major attribution of the thermocline intrusions in the AO (May and Kelley, 2002), which was responsible for the climate changes of the arctic in recent decades (Carmack et al, 1997(Carmack et al, , 2012. Moreover, due to the possible effect in the formation of the northern water masses, the double-diffusive convection might be an important factor of the global climate system.…”
Section: Introductionmentioning
confidence: 97%